Electrocardiographic Findings in Acutely and Chronically T. cruzi-infected Mice Treated by a Phenyl-Substituted Analogue of Furamidine DB569 - Elen M. de Souza; Gabriel M. Oliveira; Maria de Nazaré C. Soeiro (AboutScience Srl, 2007)
Aromatic diamidines have been successfully used to combat a wide range of parasites that cause important human infections. Recently we reported that a N-phenyl-substituted analogue of furamidine (DB569) exerts a micromolar trypanocidal activity against Trypanosoma cruzi in vitro. Since DB569 also reduces the cardiac parasitism and increases the survival rates of T. cruzi-infected mice, our present aim was to analyze the potential protection of DB569 in the development of altered cardiac electrical conduction system during acute and chronic T. cruzi infection. In our experimental model of acute infection (Swiss mice inoculated with Y strain of T. cruzi), the prevailing disorder observed in electrocardiogram (ECG) analyses was sinus bradycardia. This ECG alteration was reverted in acutely infected mice treated with DB569. Interestingly, the DB569 treatment reduced signifi cantly the numbers of CD8+ T cells in the cardiac infi ltration. In addition, the noticed protection of DB569 in the ECG fi ndings of acutely-infected animals was further extended to the chronic infection. Our data suggest that the reversion to and further maintenance of normal ECG profi le in the DB569-treated infected animals may be associated with the reduced cardiac CD8+ lymphocyte infi ltration and parasitism that might be ultimately contributing to their increased survival rates.